2010
DOI: 10.1007/s10059-010-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

Abelson Virus Transformation Prevents TRAIL Expression by Inhibiting FoxO3a and NF-κB

Abstract: The Abelson Murine Leukemia Virus (A-MuLV) encodes v-Abl, an oncogenic form of the ubiquitous cellular non-receptor tyrosine kinase, c-Abl. A-MuLV specifically transforms murine B cell precursors both in vivo and in vitro. Inhibition of v-Abl by addition of the small molecule inhibitor STI-571 causes these cells to arrest in the G1 phase of the cell cycle prior to undergoing apoptosis. We found that inhibition of v-Abl activity results in upregulation of transcription of the pro-apoptotic TNF-family ligand TRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The activation of the transcription factor FoxO3a led to increased TRAIL transcription and induction of G1 arrest in the absence of v-Abl inhibition; this effect could be inhibited by the expression of a constitutively active Akt mutant in BCR-Abl-transformed human cells. Ghaffari et al [49] also demonstrated that cytokine and BCR-Abl suppression of TRAIL transcription is mediated through phosphorylation and inhibition of the FoxO3a transcription factor. This study showed that BCR-Ablinduced inhibition of TRAIL transcription is linked to the tumorigenicity in chronic myeloid leukemia [50] .…”
Section: Foxo3a Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…The activation of the transcription factor FoxO3a led to increased TRAIL transcription and induction of G1 arrest in the absence of v-Abl inhibition; this effect could be inhibited by the expression of a constitutively active Akt mutant in BCR-Abl-transformed human cells. Ghaffari et al [49] also demonstrated that cytokine and BCR-Abl suppression of TRAIL transcription is mediated through phosphorylation and inhibition of the FoxO3a transcription factor. This study showed that BCR-Ablinduced inhibition of TRAIL transcription is linked to the tumorigenicity in chronic myeloid leukemia [50] .…”
Section: Foxo3a Functionmentioning
confidence: 98%
“…Cell proliferation and apoptosis Perhaps the two most significant cellular processes that are regulated by FoxO transcription factor are the suppression of cell cycle progression and the promotion of apoptosis [46][47][48][49][50] . FoxO3a activation increases cell cycle inhibitor proteins p21 and p27, both of which subsequently suppress G1 to S cell cycle transition [51][52][53][54] .…”
Section: Foxo3a Functionmentioning
confidence: 99%
“…In acute myeloid leukemia cells, FOXO3 is in a constitutively inactive state due to its cytoplasmic localization, which is not dependent on the PI3K/Akt or ERK/MAPK pathways, instead, NF-κB, which is a key regulator of cell survival, sustains a constitutively active state (73). IκK-specific inhibition upregulates FOXO3 and tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) (74). It has also been reported that FOXO3a activates IκK/NF-κB pathways though inducing the B-cell CLL/lymphoma 10 protein (BCL10), which is an upstream regulatory factor of IκK/NF-κB (75).…”
Section: Iκb Kinase (Iκk)mentioning
confidence: 99%
“…We hypothesized that the enhanced cellular survival observed in HTLV-1 infected CD4 + T cells may be associated with the deregulation of FOXO3a signalling, given its important role in regulating cell proliferation and apoptosis in other retroviral infections [14] , [15] , [24] , [29] . We first investigated at 2 days pi the activation status of AKT, one of the upstream kinases responsible for phosphorylation of FOXO3a [23] ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of HIV-1 regulatory molecule Tat in specific T cells and macrophages also induced FOXO3a-mediated apoptosis [24] , [47] . FOXO3a activity also impacts the pathogenesis and the outcome of Abelson murine leukemia virus [29] .…”
Section: Discussionmentioning
confidence: 99%